Attenuation of corneal myofibroblast development through nanoparticle-mediated soluble transforming growth factor-β type II receptor (sTGFβRII) gene transfer - Sharma, Ajay (Molecular Vision, 2012)
PURPOSE: To explore (i) the potential of polyethylenimine (PEI)-DNA nanoparticles as a vector for delivering genes into human corneal fibroblasts, and (ii) whether the nanoparticle-mediated soluble extracellular domain of the transforming growth factor–β type II receptor (sTGFβRII) gene therapy could be used to reduce myofibroblasts and fibrosis in the cornea using an in vitro model. METHODS: PEI-DNA nanoparticles were prepared at a nitrogen-to-phosphate ratio of 30 by mixing linear PEI and a plasmid encoding sTGFβRII conjugated to the fragment crystallizable (Fc) portion of human immunoglobulin. The PEI-DNA polyplex formation was confirmed through gel retardation assay. Human corneal fibroblasts (HCFs) were generated from donor corneas; myofibroblasts and fibrosis were induced with TGFβ1 (1 ng/ml) stimulation employing serum-free conditions. The sTGFβRII conjugated to the Fc portion of human immunoglobulin gene was introduced into HCF using either PEI-DNA nanoparticles or Lipofectamine. Suitable negative and positive controls to compare selected nanoparticle and therapeutic gene efficiency were included. Delivered gene copies and mRNA (mRNA) expression were quantified with real-time quantitative PCR (qPCR) and protein with enzyme-linked immunosorbent assay (ELISA). The changes in fibrosis parameters were quantified by measuring fibrosis marker α-smooth muscle actin (SMA) mRNA and protein levels with qPCR, immunostaining, and immunoblotting. Cytotoxicity was determined using cellular viability, proliferation, and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. RESULTS: PEI readily bound to plasmids to form nanoparticular polyplexes and exhibited much greater transfection efficiency (p<0.01) than the commercial reagent Lipofectamine. The PEI-DNA-treated cultures showed 4.5×10(4) plasmid copies/µg DNA in real-time qPCR and 7,030±87 pg/ml sTGFβRII protein in ELISA analyses, whereas Lipofectamine-transfected cultures demonstrated 1.9×10(3) gene copies/µg DNA and 1,640±100 pg/ml sTGFβRII protein during these assays. The PEI-mediated sTGFβRII delivery remarkably attenuated TGFβ1-induced transdifferentiation of corneal fibroblasts to myofibroblasts in cultures, as indicated by threefold lower levels of SMA mRNA (p<0.01) and significant inhibition of SMA protein (up to 96±3%; p<0.001 compared to no-gene-delivered cultures) in immunocytochemical staining and immunoblotting. The nanoparticle-mediated delivery of sTGFβRII showed significantly better antifibrotic effects than the Lipofectamine under similar experimental conditions. However, the inhibition of myofibroblast in HCF cultures by sTGFβRII overexpression by either method was significantly higher than the naked vector transfection. Furthermore, PEI- or Lipofectamine-mediated sTGFβRII delivery into HCF did not alter cellular proliferation or phenotype at 12 and 24 h post-treatment. Nanoparticles treated with HCF showed more than 90% cellular viability and very low cell death (2–6 TUNEL+ cells), suggesting that the tested doses of PEI-nanoparticles do not induce significant cell death. CONCLUSIONS: This study demonstrated that PEI-DNA nanoparticles are an attractive vector for the development of nonviral corneal gene therapy approaches and that the sTGFβRII gene delivery into keratocytes could be used to control corneal fibrosis in vivo.